Distribution of HLA DRB1 and DQB1 alleles and DRB1-DQB1 haplotypes among Bahraini women with polycystic ovary syndrome. (September 2016) - Messadi, Amira; Malalla, Zainab H.; Al-Madhi, Safa A.; Al-Jalahma, Jawaher A.; Almawi, Wassim Y.
Highlights: HLA DRB1*10, DRB1*14, and DQB1*05 were positively associated with PCOS. HLA DRB1*11 (15.3% vs. 6.8%) was negatively associated with PCOS. DRB1*10-DQB1*05 and DRB1*14-DQB1*03 haplotypes were positively associated with PCOS. DRB1*11-DQB1*03 haplotype served a PCOS-protective role. Abstract: Objective: This study investigated the association between HLA-DRB1 and –DQB1 alleles and DRB1-DQB1 haplotypes, and polycystic ovary syndrome (PCOS) in Bahraini women. Design: Case-control, retrospective study. Methods: Study subjects comprised 80 women with PCOS, and 169 age- and ethnically-matched control women. DRB1 and DQB1 genotyping was done by PCR-SSP. Results: Of the 13 DRB1 alleles and 5 DQB1 alleles identified, DRB1*10 (14.3% vs. 4.4%) and DRB1*14 (8.7% vs. 1.1%), along with DQB1*05 (35.0% vs. 23.9%), were the most frequent alleles in cases, while DRB1*11 (15.3% vs. 6.8%) was the frequent allele found in controls. The association of PCOS with DRB1*10 ( Pc  < 0.001), DRB1*14 ( Pc  < 0.001), DQB1*05 ( Pc  = 0.040), but not DRB1*11 ( Pc  = 0.076) persisted after correcting for multiple comparisons. DRB1-DQB1 haplotype analysis identified nine common shared haplotypes in women with PCOS and control women, with a frequency exceeding 1%. Significantly higher frequency of DRB1*10-DQB1*05 (12.4% vs. 3.1%) and DRB1*14-DQB1*03 (5.6% vs. 1.0%), and reduced frequency of DRB1*11-DQB1*03 (4.1% vs. 14.1%) haplotypes were seen in women with PCOS vs. control women, thus assigning PCOS-susceptible and –protective nature to these haplotypes, respectively. This association persisted after controlling for multiple comparisons. Conclusion: Our results confirm an association of HLA-DRB1 and –DQB1 alleles and haplotypes with PCOS susceptibility in Bahraini Arabs, further underscoring the immunological/inflammatory nature of this disorder.